Studi Komputer Tentang Transien Pembukaan Pemutus Beban Pada Saluran Transmisi - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran(UI2P2) UGM, 2005)
Opening of a circuit breaker results in an electrical transient. In many cases, it produces overvoltages on electrical components involved. Because the maximum transient over voltage on load that uses the circuit breaker can be predicted, then apparatus damaged can be avoided. This research is to predict maximum circuit breaker opening transient voltage on apparatus using software that can simulate restriking transient processes. Simplification has been done in computation. Computer program was formulated using Runge-Kutta method differentiation to represent the parameter involved. Simulation results show that high dielectric strength and high interrupting capability of circuit breaker can reduce the risk of damaged of the apparatus.